Efficacy of entecavir in patients with chronic hepatitis B resistant to both lamivudine and adefovir or to lamivudine alone - Ju Hyun Shim; Dong Jin Suh; Kang Mo Kim; Young‐Suk Lim; Han Chu Lee; Young‐Hwa Chung; Yung Sang Lee (2009)
Entecavir (ETV) is currently recommended as a rescue therapy purely for adefovir (ADV)-resistant chronic hepatitis B virus (HBV) infections. We evaluated the efficacy of ETV in patients who were resistant to lamivudine (LAM)/ADV sequential therapy and in those resistant to LAM monotherapy. Fifty LAM/ADV-resistant and 38 LAM-resistant patients who received ETV 1 mg/day for at least 48 weeks were enrolled. Mean baseline serum HBV DNA and alanine aminotransferase (ALT) levels were significantly lower in the LAM/ADV-resistant group, compared with the LAM-resistant group (6.90 versus 7.62 log10 copies/mL and 102.6 versus 160.2 IU/L; both P < 0.05); hepatitis B e antigen (HBeAg) status and LAM-resistant mutation patterns were similar in the two groups. At week 48, mean reductions in HBV DNA and ALT levels were significantly less in the LAM/ADV-resistant group (−2.96 versus −4.86 log10 copies/mL and −68.3 versus −128.9 IU/L; both P < 0.05). Achievement of undetectable HBV DNA was also less common in the LAM/ADV-resistant group (10.0% versus 34.2%; P = 0.006), although the rates of HBeAg loss and ALT normalization did not differ between the two groups. Resistance to both LAM and ADV was an independent risk factor for failure of HBV DNA negativity at week 48 (odds ratio, 0.138; P = 0.019). In both LAM/ADV-resistant and LAM-resistant groups, primary responders (≥1 log decline in HBV DNA at week 12) achieved a significantly greater decrease in HBV DNA levels over the 48-week period, compared with primary nonresponders (−4.18 versus −0.97 and −5.37 versus −2.15 log10 copies/mL, respectively; both P < 0.05). Conclusion: The 48-week ETV treatment was less effective in LAM/ADV-resistant than in LAM-resistant patients. Continuing ETV monotherapy could be determined based on the virological response at 12 weeks in LAM/ADV-resistant patients. (Hepatology 2009.)